Characterization of a novel MYO3A missense mutation associated with a dominant form of late onset hearing loss - Dantas, Vitor G. L. (Sci Rep, 2018)
Whole-exome sequencing of samples from affected members of two unrelated families with late-onset non-syndromic hearing loss revealed a novel mutation (c.2090 T > G; NM_017433) in MYO3A. The mutation was confirmed in 36 affected individuals, showing autosomal dominant inheritance. The mutation alters a single residue (L697W or p.Leu697Trp) in the motor domain of the stereocilia protein MYO3A, leading to a reduction in ATPase activity, motility, and an increase in actin affinity. MYO3A-L697W showed reduced filopodial actin protrusion initiation in COS7 cells, and a predominant tipward accumulation at filopodia and stereocilia when coexpressed with wild-type MYO3A and espin-1, an actin-regulatory MYO3A cargo. The combined higher actin affinity and duty ratio of the mutant myosin cause increased retention time at stereocilia tips, resulting in the displacement of the wild-type MYO3A protein, which may impact cargo transport, stereocilia length, and mechanotransduction. The dominant negative effect of the altered myosin function explains the dominant inheritance of deafness.